2022
DOI: 10.1017/s1092852922000840
|View full text |Cite
|
Sign up to set email alerts
|

Kynurenine pathway and autism spectrum phenotypes: an investigation among adults with autism spectrum disorder and their first-degree relatives

Abstract: Background Increasing literature highlighted alterations of tryptophan (TRP) metabolism and kynurenine (KYN) pathway in children with autism spectrum disorder (ASD). However, no study specifically focused on adult samples. Meanwhile, several authors stressed the relevance of investigating neurobiological correlates of adult forms of ASD and of those subthreshold ASD manifestations frequently found in relatives of ASD probands, known as broad autism phenotype (BAP). This work aimed to evaluate circulating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 95 publications
0
18
0
Order By: Relevance
“…Some studies found a significant elevation in serum and urinary levels of the neurotoxic XA and QA (Gevi et al, 2016;Lim et al, 2016), while other studies revealed no significant difference in QA between ASD and controls (Bryn, Verkerk, et al, 2017;Ormstad, Bryn, Verkerk, et al, 2018). Another study conducted on platelet-rich plasma found no significant difference in QA between the study groups (Carpita et al, 2022).…”
Section: Neurotoxic Trycats In Asdmentioning
confidence: 98%
See 1 more Smart Citation
“…Some studies found a significant elevation in serum and urinary levels of the neurotoxic XA and QA (Gevi et al, 2016;Lim et al, 2016), while other studies revealed no significant difference in QA between ASD and controls (Bryn, Verkerk, et al, 2017;Ormstad, Bryn, Verkerk, et al, 2018). Another study conducted on platelet-rich plasma found no significant difference in QA between the study groups (Carpita et al, 2022).…”
Section: Neurotoxic Trycats In Asdmentioning
confidence: 98%
“…Intriguingly, researchers have discovered that several TRYCATs are considerably altered in ASD, including elevated serum QA and KA levels (Bilgiç et al, 2022; Lim et al, 2016), whereas other studies reported significantly lower QA and KA levels in ASD (Bryn, Verkerk, et al, 2017; Carpita et al, 2022; Ormstad, Bryn, Verkerk, et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Carpita et al investigated the changes in KP metabolites in ASD adults, and they found significantly lower levels of Trp and QUIN and no changes in Kyn and Kyna [ 2 ]. Recently, a meta-analysis comprising all KP metabolites and keywords related to maternal pregnancy and the fetal outcome showed that an altered KP metabolite concentration is significantly related to a high risk of preeclampsia, fetal growth restriction, and preterm birth [ 129 ].…”
Section: Perinatal Kp Metabolismmentioning
confidence: 99%
“…These are all considered risk factors for ASD [ 204 , 205 , 206 ]. Even though single compound changes of KP are still controversial in each clinical study ( Table 1 ) [ 1 , 2 , 8 , 207 , 208 , 209 , 210 , 211 , 212 , 213 , 214 , 215 , 216 , 217 , 218 , 219 ], it is clear that an abnormal balance of KP metabolites may be associated with adverse fetal neurodevelopment and the pathogenesis of ASD.…”
Section: Perinatal Kp Metabolismmentioning
confidence: 99%
See 1 more Smart Citation